Development of the Acid and Base E-Module Based on Contextual Teaching And Learning for Class XI SMA/MA - Listia, Herfina; Andromeda, Andromeda (FKIP - Universitas Riau, 2022)
Acids and bases are one of the chemistry learning materials that are studied in class XI SMA/MA. Acids and bases are contextual and have a lot of relevance in everyday life. Additionally, acids and bases are prerequisites for studying some other chemistry. Therefore, appropriate learning models or strategies and teaching materials are needed. One of them is the use of contextual learning-based e-modules. This study aims to determine the validity, practicality, and on effectiveness of developing an acid-base e-module based on contextual teaching and learning for class XI SMA/MA. This form of study is an educational design research that uses the Plomp model which consists of three stages, namely the preliminary research, the prototyping phase, and the assessment phase. The assessment phase is not carried out. The results showed that e-modules had content, construct, and media validity values of 0.87, 0.88, and 0.89 respectively with valid categories, practicality according to teachers 88.52% with very practical categories and practicality according to students 85.10% with practical category. The average N-gain value for the effectiveness test is 0.7 with the high effectiveness category. The results of this study indicate that the developed e-module is valid, practical, and effective.